Influence of Lecturer's Pedagogic Competency Level, Quality of Administrative Services, Completeness of Lecture Supporting Facilities, and Student Satisfaction on Learning Motivation - Sumarsono, Raden Bambang; Gunawan, Imam; Kusumaningrum, Desi Eri; Benty, Djum Djum Noor; Bhayangkara, Athalla Nauval (Jurnal Ilmu Pendidikan, 2021)
This research aims to know students' perceptions of the competencies of pedagogical lecturers, the quality of administrative services, the completeness of the facilities supporting lectures, student satisfaction and its relationship with the motivation of student learning. The approach used is quantitative with the design of survey research. The research population was 3,702 of FIP UM students, while the sample was 361 students. The study was conducted in 2020. Sampling techniques using proportional sampling and simple random sampling. Data collection using questionnaires, meanwhile for data analysis using two kinds of analysis techniques, namely descriptive analysis and path analysis. The results showed: (1) the competency of pedagogic lecturers, and the quality of administrative services according to the perception of students in the category is quite good, while the student's perception of the completeness of the lecture support facilities in the category is quite complete, the student expresses satisfaction for the services received. But on the motivation of studying of FIP students have a low level; (2) there is an influence on the level of pedagogical competency of lecturers on the motivation of student learning; (3) there is an influence on the quality of administrative services on student learning motivation; (4) there is an influence on the completeness of the facilities to support lectures on the motivation of student learning; (5) there is an influence of satisfaction on the motivation of student learning; and (6) simultaneously there is the influence of lecturer competency level, quality of administrative services, completeness of lecture support facilities, and student satisfaction on learning motivation.